Study on Genetic Variance of miR-541 in Type 1 Diabetes. (11th December 2012) - Han, Bei; Shi, Xing; Peng, Quan; Gao, Wentao
Abstract : Genetic susceptibility plays a key role in type 1 diabetes development. Because miR-541 gene was located within the associated chromosome loci and its target genes include the diabetes-associated gene neurogenin3, this study aimed to investigate whether miR-541 had type 1 diabetes-associated genetic variations. Type 1 diabetes children and healthy volunteers were recruited; direct sequencing was performed in initial 69 patients and 46 volunteers. We identified 1 reported SNP (rs12893725) and 3 novel genetic variations, for the candidate -404 G→T variation, restriction fragment length polymorphism (RFLP) was performed in total 247 diabetes children and 212 healthy volunteers, a different distribution trait of allele frequencies was found between the two groups, and further clinical analysis found no significant correlation between clinical parameter and genotypes among patients. In addition, by luciferase reporter assay, -404 was found to be within putative promoter region of pre-miR-541; although mutation of G→T has no effect on promoter activity, a significant secondary structure alteration may possibly influence its processing and transcription. In conclusion, we identified 3 novel genetic variations in putative promoter of miR-541 in type 1 diabetes patients; -404 G→T of miR-541 is a potential T1D-associated genetic variation.